CACNA1C (CaV1.2) and other L-type calcium channels in the pathophysiology and treatment of psychiatric disorders: Advances from functional genomics and pharmacoepidemiology. (1st December 2022) - Harrison, Paul J.; Husain, Syed M.; Lee, Hami; Los Angeles, Alejandro De; Colbourne, Lucy; Mould, Arne; Hall, Nicola A.L.; Haerty, Wilfried; Tunbridge, Elizabeth M.
Abstract: A role for voltage-gated calcium channels (VGCCs) in psychiatric disorders has long been postulated as part of a broader involvement of intracellular calcium signalling. However, the data were inconclusive and hard to interpret. We review three areas of research that have markedly advanced the field. First, there is now robust genomic evidence that common variants in VGCC subunit genes, notably CACNA1C which encodes the L-type calcium channel (LTCC) CaV 1.2 subunit, are trans-diagnostically associated with psychiatric disorders including schizophrenia and bipolar disorder. Rare variants in these genes also contribute to the risk. Second, pharmacoepidemiological evidence supports the possibility that calcium channel blockers, which target LTCCs, might have beneficial effects on the onset or course of these disorders. This is especially true for calcium channel blockers that are brain penetrant. Third, long-range sequencing is revealing the repertoire of full-length LTCC transcript isoforms. Many novel and abundant CACNA1C isoforms have been identified in human and mouse brain, including some which are enriched compared to heart or aorta, and predicted to encode channels with differing functional and pharmacological properties. These isoforms may contribute to the molecular mechanisms of genetic association to psychiatric disorders. They may also enable development of therapeutic agents that can preferentially target brain LTCC isoforms and be of potential value for psychiatric indications. Highlights: CACNA1C and other L-type voltage gated calcium channel subunit genes are associated with risk for neuropsychiatric disorders. The molecular mechanism of genetic association likely involves altered expression and splicing. Dihydropyridine calcium channel blockers, especially brain-penetrant agents, may have some beneficial effects on risk of these disorders. Long-range RNA sequencing reveals a distinct repertoire of CACNA1C isoforms in brain. Brain-enriched CACNA1C isoforms may represent novel targets for psychotropic medication.